(untitled) (American International Journal of Agricultural Studies, 2022)
The general acceptability of waterleaf and its profitability as a vegetable has promoted its high demand in Nigeria. However, rural farmers depend on conventional farming systems for production with a low output. This calls for an alternative technique besides the conventional method to boost production and meet market demand. This study, therefore, evaluated the yield response of waterleaf cuttings to soil and soilless systems. Single and double nodal cuttings were cut from one-month-old waterleaf plants and planted in 4 kg cocopeat substrate and topsoil each, mixed with 250 g poultry manure each and arranged in a 2 (level of nodal cuttings) by 2 (substrate) factorial experiment laid in a completely randomized design with three replicates in 2 cycles. The plants were watered every other day. At harvest, data were collected on the Root Weight (RW), Shoot Weight (SW), and Leaf Weight (LW). Data collected were analyzed using ANOVA and differences in means were separated using least significance differences at 5% significance level. The substrate type was insignificant in the growth and yield parameters. However, the RW, SW and LW differed significantly between the nodal cuttings and ranged from 9.1±2.8 g to 21.2±2.8 g, 12.0±4.5 g to 27.0±4.5 g and 10.7±3.1 g to 21.9±3.1 g, respectively in the first cycle. The RW, SW and LW, also ranged from 10.1±1.8 g to 20.5±1.8 g, 12.7±3.0 g to 24.8±3.0 g, and 11.7±3.0 g to 23.7±3.0 g in the second cycle of production. JEL Classification Codes: Q16.